UJI EFEK HIPOGLIKEMIK EKSTRAK KLOROFORM DAN n-BUTANOL DAUN BELIMBING WULUH (Averrhoa bilimbi L.) PADA MENCIT (Mus musculus) YANG DIINDUKSI ALOKSAN - Rachmat Kosman (As-Syifaa Jurnal Farmasi, 2012)
The research About, Hypoglycemic Effect Test Extracts Chloroform and n-Butanol Leaf Belimbing Wuluh (Averrhoa bilimbi L.) Against Mice (Mus musculus) The Induced by Aloksan. This absorvation is done withaim to determine the hypoglycemic of test chloroform and n-butanol leaf belimbing wuluh (Averrhoa bilimbi L.) against mice (Mus musculus) with the main aloksan. This animal abservatian try to inductied. With aloction with the aim to destroy sel-β pancreas and try to rise the animal blood glucose rate. This research utilized 18 male mice divided into 6 groups, each group consisted of 3 male mice. Groop I was given 0,182 gram/kgBB of chloroform extract, groop II was given 0,091 gram/kgBB chloroform extract, groop III was given 0,182 gram/kgBB n-butanol extract and groop IV was given 0,091 gram/kgBB n-butanol extract, and groop V was the positif comparison groop that given glybenclamide sespention and groop VI is the groop with negative control that was given Na CMC 1%. It  was given by feeded with volume of 1 ml/ 30 gBB. The abservatian reault shaw that chloroform ekstrak and n-butanol belimbing wuluh leat (Averrhoa bilimbi L.) has the effect to deerease glucose blood to mice (Mus musculus).Key Words : Hipoglycemic, Avverhoa bilimbi, Aloxan